Tumor lysis-like syndrome in a child during treatment for visceral leishmaniasis. (September 2016) - Tragiannidis, Athanasios; Papageorgiou, Maria; Stamou, Maria; Hatzipantelis, Emmanuel; Papageorgiou, Theodotis; Giannopoulos, Andreas; Damianidou, Lamprini; Pappa, Anna; Pappa, Stiliani; Hatzistilianou, Maria
A 2.5-year-old girl was admitted due to splenomegaly and pancytopenia. Laboratory analysis revealed pancytopenia and hypergammaglobulinemia, and due to the absence of fever and the relevant clinical and hematological presentation the child was initially suspected for acute lymphoblastic leukemia. Bone marrow aspiration displayed macrophages and extracellular space containing Leishmania amastigotes. Visceral leishmaniasis diagnosis due to Leishmania infantum was confirmed by the presence of high titers of Leishmania antibodies and by PCR. The patient was successfully treated with liposomal amphotericin B but during the third post-treatment day significant increases in the levels of serum uric acid, blood urea nitrogen, and phosphate were registered. The child was successfully treated with hydration and urine alkalization and resulted in full recovery of the metabolic abnormalities.